Field Trial and Agronomic Performance of Antibiotics in Naturally-Colored Cotton Against Key Leaf Damaging Pests - Praparat Hormchan,; Arunee Wongpiyasatid, (Agriculture and Natural Resources, 2008)
Laboratory tests were conducted to acquire the antibiotic effect of white and naturally-colored cotton varieties/lines, AP2, PM1 and PM4 compared to the control, SR60, using fresh leaves fed to the 3rd instar Helicoverpa armigera larvae. There were no significant differences found in the developmental times and weights of the bollworm larvae and pupae fed on the leaves of the different cotton varieties/lines except for the percentage of adult abnormalities in PM1and PM4. The leaf damage by the leafhoppers was undertaken in a greenhouse using adult and nymph leafhoppers released in a screen cage containing one month-old cotton plants of each variety/line grown in pots. After 14 days, the results revealed that AP2 had the lowest score for hopperburn rating (3.5). Cotton variety trials in sprayed and unsprayed plots were conducted during 2006 and 2007 at two locations, the Field Crop Research Center at Nakhon Ratchasima and a farmer’s field at Thongpapoom, Kanchanaburi. The mean annual number of key pests and the annual yield of each variety/line at each location were compared and the average agronomic performance of each variety/line was HVI analyzed. At Nakhon Ratchasima, leafhoppers were more abundant than aphids and whiteflies in both 2006 and 2007. There was a significant difference in the mean leafhopper numbers for AP2 and PM4 between both plots during the two years, while for PM1 there was a significant difference in 2007 only. Seed weights of SR60 and PM1 differed between the sprayed and unsprayed plots in 2006. At Tongpapoom, Kanchanaburi, both SR60 and PM4 in 2006, and PM4 again in 2007 had significantly different amounts of leafhopper between the sprayed and unsprayed plots. The yield of SR60 in the sprayed plot significantly differed from the unsprayed plots in 2006. Agronomic performance of each cotton fiber found only micronaire range in PM1 from Thongpapoom and the fiber lengths of SR60, AP2 and PM1 grown at Nakhon Ratchasima to be designated as premium. At Tongpapoom, the AP2 fiber length fell in the base range. The percent lint of AP2 was the highest at Nakhon Ratchasima, while PM4 had the lowest value for this parameter at both locations.